Preclinical Substantiation of the Use of Implants for Osteosynthesis from Carbon-Carbon Composite Material - Holovakha, M.L.; Chornyi, V.V. (TERRA ORTHOPAEDICA, 2022)
Background. Metals used for the manufacture of various implants for traumatology have all the necessary mechanical properties, but these materials are able to oxidize. In comparison, carbon has excellent biocompatibility. Carbon-carbon composite material (CCCM) is 2-4 times lighter than a similar metal implant, has a stiffness and modulus of elasticity close to similar indicators of a human bone, not prone to the effect of fatigue stress, and is characterized by chemical resistance in the body and high biocompatibility. Objective. The purpose of this work was to evaluate the features of bone regeneration according to pathomorphological analysis in an experiment on animals. Material and Methods. Carbon-carbon composite material for intromedular osteosynthesis after experimental fracture on white outbred male Wistar rats (n=18) was used in the experiment. A stainless steel rod (n=18) was used for control. Subsequently, rats of both groups were kept in standard vivarium conditions. Results. Histological examination revealed that the use of implants with CCCM did not disrupt vascularization and angiogenesis in the fracture zones. During the analysis of the contact of bone tissue and implant material, it was determined that in the larger area of ​​the perimeter of the pin with CCCM, a newly formed bone was located directly on its surface, filling its irregularities. In the case of the use of stainless steel rods, a significant number of lymphocytes were accumulated around the newly formed blood vessels directly adjacent to small hemorrhages, which were always observed at the fracture site. Conclusions. Regeneration of an experimental rat femur fracture after osteosynthesis with carbon-carbon composite implants did not differ significantly from fracture fusion after osteosynthesis with a stainless steel implant.